Beyond Technocentrism: A Tripartite Framework for Humanizing AI Integrated Scientific Modeling in Climate-Related Geography Education - Muhammad Khairul; Nurul Saminan (Equator Science Journal, 2025)
This study aims to explore how critically designed digital content can foster spatial-social reasoning and critical thinking in Geography education within AI-integrated learning environments. Using a systematic literature review method based on a modified PRISMA protocol, 35 peer-reviewed studies (2000–2024) were selected from Scopus, SINTA, and Google Scholar databases. The analysis employed thematic coding and critical interpretive synthesis to examine four pedagogical dimensions: digital interactivity, spatial-social reasoning, AI personalization, and critical-reflective pedagogy. Findings reveal that digital content can act as an epistemological scaffold through three core functions: as a cognitive tool for spatial inquiry, a medium for ethical deliberation, and a dialogic platform for collaborative knowledge-building. Quantitative gains were observed in spatial literacy (32–47%), ethical awareness, and metacognitive regulation when digital tools were integrated within authentic and justice-oriented learning contexts. The study highlights the value of a tripartite pedagogical framework that bridges connectivism and Freirean critical pedagogy, particularly in Global South education. It also underscores the urgency of embedding AI ethics and critical digital pedagogy in teacher training and curriculum reform. These findings suggest that transformative learning outcomes are achievable when technology is positioned not merely as a delivery tool, but as a dialectical medium for democratic, contextual, and ethical education.